Effects of Blended Simulation on Nursing Students' Critical Thinking Skills: A Quantitative Study - Anders Sterner PhD, RN; Robert Sköld MSc, RN; Henrik Andersson PhD, RN (SAGE Publishing, 2023)
Introduction Critical thinking is regarded as imperative to healthcare quality and patient outcomes; therefore, effective strategies in nursing education are required to promote students' critical thinking abilities, leading to their success in clinical work. Accordingly, simulation-based education has been suggested as a measure for achieving this goal. Objective The aim of this study was to explore whether a nursing education course with blended simulation activities (hands-on simulations with high-fidelity manikins and a web-based interactive simulation program) could increase nursing students' critical thinking skills. Method A quasiexperimental, one-group pretest and post-test design was utilized. Data were collected through premeasurement and postmeasurement using a critical thinking questionnaire and were analyzed using paired sample t -tests, independent sample t -tests, and the nonparametric Wilcoxon signed-rank test. The effect size was calculated using Cohen's d formula. Results Sixty-one nursing students (57 women and four men, mean age 30 years) participated in the study. Findings of the paired sample t -test showed a significantly higher mean score for posteducation than pre-education, indicating a significant change in nurses' critical thinking capabilities ( p  < .001). The results for Cohen's d formula ( − 0.87) of the mean scores between pre-education and posteducation indicated a large effect size. The Wilcoxon signed-rank test also showed a statistically significant increase in the students' critical thinking abilities between pre-education and posteducation measures ( p  < .001). No statistically significant differences were found in the mean score according to age or sex. Conclusion This study concluded that blended simulation-based education can increase nursing students' critical thinking capabilities. As a result, this study builds on the use of simulation as a measure for developing and promoting critical thinking abilities during nursing education.